Formação e caracterização de eletrodepósitos de cobre, cobalto-cobre e multicamadas cobalto-cobre a partir de baterias de íon-Li exauridas - Celante, Vinicius Guilherme (2009)
In this work the processes of formation and characterization of electrodeposits of copper, Cu and Co-Co-Cu multilayer from the recycling of exhausted batteries to Li-ion were studied. For the electrodeposition of copper, the charge efficiency is obtained in the range 3.0 to 5.0 C cm-2, with about 98.0% at pH values of 2.0 and 4.5. For measures of EQCM for copper, there is a simultaneous mechanism between the direct deposition and reduction from Cu+. In both conditions of pH, the presence of Cu2O is caused by alkalinization of the interface electrode/solution. The equivalent circuit of the system, obtained by EIS resulted in Rs(RpQ)W. The presence of diffusional element W is on the diffusion of H+ ions from solution to the pores of the electrodeposits. The constant phase element is associated with the surface heterogeneity. The SEM measures resulted in the areas of micro and macroporosity. EDS analysis observed that the surface is composed mostly of copper. Measures of XRD at pH = 2.0 and 4.5 resulted in the directions [111] and [200], related to FCC structure of metallic copper, with the presence of the direction [002] of Cu2O. With the increase of the charge density, there is a decrease in the relative intensity peaks of metallic copper and the detection of the direction [110] also related to Cu2O. The electrodeposition of Co-Cu resulted in a mechanism of deposition of Co with formation of Co(OH)2 and copper in the presence of Cu+. The equivalent circuit obtained was Rs(RpQ)W, with W on the diffusion of H+ions from bulk phase to the interface metal/electrode. The characterization by SEM resulted in microporous electrodeposits at pH = 2.7 and microporosity and perpendicular growth to the substrate at pH = 5.4. For the technique of EDS, there was a quantity of Co and Cu approximately 2 times greater on the surface at pH = 2.7 than at pH = 5.4. The crystallographic directions obtained by XRD show both the copper and cobalt preferably electrodeposits on the FCC structure. The Co-Cu multilayers were studied on different substrates (Al, Pt and GC). Measures of EIS presented an inductor L in the equivalent circuit Rs(RpQ)L, related to the dissolution of the cobalt deposit. Measures of SEM, EDS and XRD showed that at pH = 2.7 the electrodeposits occur preferentially by 2D growth with higher coating and at pH = 5.4 a simultaneous 2D and 3D growth, with areas of micro and macroporosity. The deposits are mostly formed by Co and Cu, and detected the substrate of Al. Both copper and cobalt are deposited on FCC structure.